QUALITY CONTROL OF EDEL COCOA (COCOA PRECIOUS) AT PT. PERKEBUNAN NUSANTARA XII (PERSERO) BANJARSARI GARDEN JEMBER REGENCY - Dwi Putri Jeng Ivo Nurun Nisa'; Mohamad Harisudin; Isti Khomah (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
This research aims to (1) knowing the defects of the edel cocoa beans (2) knowing the defects of the edel cocoa beans in the Banjarsari garden were still within the control limit or not (3) knowing the dominant defects, and (4) analyzing the causes and proposed actions to improve the defects of the edel cocoa beans in PTPN XII (Persero) Kebun Banjarsari. The basic method of research is descriptive analytical. The method of determining key informants and respondents was carried out by purposive sampling. The results showed that (1) The defects of the edel cocoa beans consisted of 2753.2 kg of prongkol beans, 2143.2 kg of broken beans, 1898.47 kg of black skin seeds, 1667.34 kg of cocoa beans, moldy seeds (moldy) as much as 34.193 kg, and insect seeds as much as 0.69 kg. (2) Chart analysis found that the quality tolerance limits of edel cocoa beans varied for 5 years, Deviation of defects in edel cocoa occurred in the 9th month (September 2015) and the 53rd month (August 2019). (3) Pareto diagram analysis, the dominant defects in edel cocoa beans are prongkol, crushed beans and black skin beans. (4) The Fishbone diagram identifies the factors that cause edel cocoa bean defects are method, human, material, environment. Proposed remedial action for each of the factors must be implemented immediately to overcome the dominant damage problem. The recommendation given is to hold routine training at least once a month, the company to take alternative actions by planting diversified cover crops, improving cleanliness regularly, performing sanitation and cleaning weeds around the garden area.